Los salvajes en el cine : notas sobre un mito en movimiento - Bartra, Roger, 1942-; Villadelángel Viñas, Gerardo (Ciudad de México : INAH : Fondo de Cultura Económica : La Jaula Abierta, 2018)
In The savages in cinema, Roger Bartra shows us how the mythical savages keep invading the western civilization and have gotten used to the new scientific and technological landscapes. The guiding thread of this work is the mythical condition of these characters that have existed in the Western imagination for millenniums and that in the cinema they acquired certain particular characteristics, here we see vampires, werewolves, mummies, cyborgs, robots, superheroes and others.
Prólogo -- Monstruos y salvajes reales -- La invención del salvaje prehistórico -- Superhéroes bestiales -- Ciborgs salvajes -- Estados primigenios -- Licantropía -- El salvaje noble -- Planetas agrestes -- Reflexiones finales.
Includes filmography (pages 156-174).
Incluye referencias bibliográficas.
In Spanish.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2021. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Violence in motion pictures; Violencia en películas.; Masculinidad en las películas.; Hombres salvajes; Masculinity in motion pictures; Wild men; Libros electrónicos.